Concepts of Sakinah, Mawaddah And Warrahmah Families According to Guru Sekumpul - Khairunnisa, Ririn; Hasanah, Uswatun; Attamimi, Taufik Abdullah; Della, Dhia Alfa (Journal Analytica Islamica, 2025)
Muhammad Zaini bin Abdul Ghani Al Banjari or known as Guru Sekumpul is a respected scholar who comes from the Sekumpul area, Martapura, South Kalimantan. He often held a knowledge assembly (pengajian) which was always attended by tens of thousands of people and became a role model in the practice of Islamic teachings for the community, especially in South Kalimantan. One of the topics discussed and very crucial for people's lives is the concept of a sakinah family, mawaddah warrahmah. Given the great influence of Guru Sekumpul in the community, this study aims to find out the concept of sakinah family, mawaddah warrahmah according to Guru Sekumpul. This study is a literature study using qualitative descriptive analysis. The results and conclusions of this study indicate that the Sakinah mawaddah, warrahmah family according to Guru Sekumpul is with the creation of the concept of “baitii jannatii” (my house my heaven) through three things namely; 1) Mutual respect for each other, namely when there are shortcomings both on the part of the wife and husband, it is not allowed to complain but must understand and complement each other. 2) Fulfilling the rights of husbands and wives, namely when the rights of both have been fulfilled, it will create a sense of belonging to each other.  3) Carrying out the obligations of husband and wife, where when the obligations of both have been carried out, their rights have automatically been fulfilled.